2020
DOI: 10.1093/mnras/staa2765
|View full text |Cite
|
Sign up to set email alerts
|

G107.0+9.0: a new large optically bright, radio, and X-Ray faint galactic supernova remnant in Cepheus

Abstract: Wide-field Hα images of the Galactic plane have revealed a new supernova remnant (SNR) nearly three degrees in diameter centred at l = 107.0, b = +9.0. Deep and higher resolution Hα and [O III] 5007 Å images show dozens of Hα filaments along the remnant’s northern, western, and southwestern limbs, but few [O III] bright filaments. The nebula is well detected in the Hα Virginia Tech Spectral-Line Survey images, with many of its brighter filaments even visible on Digital Sky Survey images. Low-dispersion spectra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 59 publications
7
21
0
Order By: Relevance
“…Its distance is 900 pc based on its dispersion measure. Thus, the pulsar is closer than G107.0+9.0 according to the 1.5 kpc to 2 kpc distance quoted by Fesen et al (2020). Its smaller absolute RM is in accordance with that of extragalactic sources, which trace the magnetised interstellar medium throughout the entire Galactic disk, and indicate a magnetic field direction pointing away from us throughout the Galaxy.…”
Section: Polarised Emissionsupporting
confidence: 71%
See 4 more Smart Citations
“…Its distance is 900 pc based on its dispersion measure. Thus, the pulsar is closer than G107.0+9.0 according to the 1.5 kpc to 2 kpc distance quoted by Fesen et al (2020). Its smaller absolute RM is in accordance with that of extragalactic sources, which trace the magnetised interstellar medium throughout the entire Galactic disk, and indicate a magnetic field direction pointing away from us throughout the Galaxy.…”
Section: Polarised Emissionsupporting
confidence: 71%
“…When searching for faint planetary nebula, Yuan & Liu (2013) noticed Hα emission from an almost spherical object with a diameter of about 3 • , which they proposed to be a so far unidentified supernova remnant (SNR). Fesen et al (2020) confirmed G107.0+9.0 as an SNR based on optical imaging in several lines and spectroscopic observations, which revealed shock velocities between 70 km s −1 and 100 km s −1 . Fesen et al (2020) estimated the distance of G107.0+9.0 between 1.5 kpc and 2 kpc, implying a size of 75 pc to 100 pc.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations